2023
DOI: 10.3390/nu15030771
|View full text |Cite
|
Sign up to set email alerts
|

Global Dietary and Herbal Supplement Use during COVID-19—A Scoping Review

Abstract: During the first year of the COVID-19 pandemic, the lack of cure and the intensity of the global spread raised a common awareness of health. The aim of this scoping review is to summarize dietary supplement use globally during first two years of the COVID-19 pandemic. A systematic search was conducted in December 2021 following PRISMA guidelines. PubMed, ERIC, and Scopus databases were searched, and 956 results were screened for eligibility. Fourteen cross-sectional studies from 11 countries and 3 continents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Since the onset of COVID-19 pandemics, the use of supplements believed to strengthen the immune system has increased with vitamin C, zinc, multivitamins and vitamin D being the most popular among vitamins and trace elements [27 ▪ ]. Recent evidence showed that micronutrient supplementation, especially vitamin D, vitamin A and zinc, may prevent and have a positive effect on the course of respiratory infection which encourages a similar approach for COVID-19 [28–31].…”
Section: Micronutrients and Coronavirus Disease 2019mentioning
confidence: 99%
“…Since the onset of COVID-19 pandemics, the use of supplements believed to strengthen the immune system has increased with vitamin C, zinc, multivitamins and vitamin D being the most popular among vitamins and trace elements [27 ▪ ]. Recent evidence showed that micronutrient supplementation, especially vitamin D, vitamin A and zinc, may prevent and have a positive effect on the course of respiratory infection which encourages a similar approach for COVID-19 [28–31].…”
Section: Micronutrients and Coronavirus Disease 2019mentioning
confidence: 99%
“…There are also several types of herbal supplements/natural products which have been considered as they may act against diverse infections, including COVID-19 [17]. The most widely used are ginger, garlic, honey, turmeric (curcumin), lemon, black seed, cinnamon, and anise.…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…Symptomatic treatment of long‐COVID is mostly based on prescribed antiviral, anti‐inflammatory drugs for COVID‐19, however, often these drugs fail to counter the relapsing symptoms (Yong, 2021). That is why, in search of a remedy for symptom relief, patients and also doctors are turning toward over‐the‐counter non‐pharmaceutical products, like dietary supplements, that can play the role of treatment adjuvants (Arora et al, 2023).…”
Section: Facts About Covid‐19 Along With Its Severity Risk Of Organ D...mentioning
confidence: 99%